Effects of UV-B radiation and water stress on chlorophyll fluorescence parameters and activity of xanthophyll cycle in leaves of sessile oak (Quercus petraea) seedlings - Szőllősi, Erzsébet (Acta Biologica Szegediensis, 2008)
In the present study we investigated the photosynthetic responses of sessile oak seedlings to UV-B radiation and water stress in growth chamber experiment. Seedlings of sessile oak showed sensitivity to enhanced UV-B radiation which appeared in decreases of maximum photochemical efficiency (Fv/Fm) and actual photochemical efficiency of PSII ($F/Fm’). UV-B radiation and water stress induced 150 and 170 % increase of non-photochemical fluorescence quenching (NPQ) and threefold and fourfold elevation of activity of xanthophyll cycle as compared to the control, respectively. Seedlings exposed simultaneously to UV-B and water stress induced larger decrease of Fv/Fm, $F/Fm’ and RFD than those exposed separately to enhanced UV-B or water withdrawal as compared to control plants. Both UV-B radiation and water stress increased non-photochemical quenching with a parallel enhancement of zeaxanthin formation.